THE EFFECT OF APPLICATION OF GRANULAR ORGANIC FERTILIZER ON PEST RESISTANCE AND PRODUCTIVITY OF THREE RED ONION CULTIVARS (Allium ascalonicum L.) - Tabita Karismawati; Ellen Rosyelina Sasmita; Rukmowati Brotodjojo (Jurnal Agrivet, 2018)
The aim of this research was to know the effect of granular organic fertilizer enriched with boiler ash and neem leaves powder on productivity and pest resistance of three red onion cultivars (Allium ascalonicum L.). The research was conducted in coastel sandy soils in Srigading village, Sanden, Bantul, DIY, from June to August 2017. The experiment was arranged in a Completly Randomized Block Design with two factors. The first factor was the doses of granular organic fertilizer (20 ton/ha, 30 ton/ha and 40 ton/ha) and anorganic fertilizer as control. The second factor was red onion cultivars (Super Biru, Crok Kuning and Tiron). Parameters observed included plant height, number of bulblets, number of leaves, pest population, damage intensity, number of bulbs, fresh weight of bulbs, fresh weight of bulbs per plot, economical weight of dried bulbs per plot and economical weight of dried bulbs per hectare. The data were subjected to Anova and followed by Duncan’s Multiple Range Test at 5%. The results showed interaction between red onion cultivars and granular organic fertilizer significantly increased the number of bulblets, number of bulbs, fresh weight of bulbs, fresh weight of bulbs per plot, economical weight of dried bulbs per plot and economical weight of dried bulbs per hectare. The pest founded in this research was Spodoptera exigua. Pest population and damage intensity were not significantly effected by red onion cultivars and granular organic fertilizer treatment. The result showed the application of 40 ton/ha on Crok Kuning cultivar and Tiron cultivar resulted in the highest red onion production.Keywords: granular organik fertilizer, red onion, pest